Organic Egg Consumption: A Systematic Review of Aspects Related to Human Health - Mesas, Arthur Eumann; Fernández-Rodríguez, Rubén; Martínez-Vizcaíno, Vicente; López-Gil, José Francisco; Fernández-Franco, Sofía; Bizzozero-Peroni, Bruno; Garrido-Miguel, Miriam (Frontiers in Nutrition, 2022)
Consumption of organic foods has increased recently, but evidence about their potential health benefits is still limited. This systematic review synthesizes the available scientific evidence on the association between organic egg consumption and human health. We searched for peer-reviewed articles on this subject indexed in the MEDLINE, EMBASE, Web of Science and Cochrane Library databases from the inception date to April 13, 2022. This review is based on PRISMA guideline recommendations. Three studies on organic egg consumption in humans were included. In a randomized crossover trial, after 8 weeks of consuming organic eggs, participants had higher serum concentrations of the beta-carotene lutein compared to the period without consuming eggs. In a cross-sectional design study with nationally representative data from Americans over the age of 50, it was found that consumption of organic eggs was associated with lower levels of the inflammatory markers C-reactive protein and cystine C. Finally, in a cohort of children aged 0 to 2 years, no association was observed between consuming organic eggs and the risk of eczema. In conclusion, the evidence about the potential benefits of organic egg consumption and human health is promising but still requires further research. A human research agenda is proposed based on laboratory studies pointing out that organic eggs have a better nutritional profile than conventional eggs.